Adsorptive removal of methyl orange from aqueous solutions with natural Garmak clay as cheap and efficient adsorbent in batch and continuous systems - Babakr, Karukh Ali; Aziz, Bakhtyar Kamal (Sulaimani Journal for Pure and Applied Sciences, 2019)
The natural clay of North Garmak-Sulaimani was characterized with XRF, XRD and FTIR. The specific surface area (18.8 m2 g-1) was determined with N2 gas adsorption analyzer using multi-point BET isotherm and 0.054 cc g-1 total pore volume. The cation exchange capacity was estimated as 12.4 mmol/100 g of the natural clay by the method of Cu-triene complex. The efficiency of the natural clay was evaluated for the adsorption of a model anionic dye (methyl orange) in batch system. Non-linear curve fitting was used to examine the kinetic and equilibrium experimental data for appropriate model. Langmuir, Freundlich and Temkin isotherms were fitted well to the experimental data. The best fit was with Langmuir model with a monolayer adsorption capacity of 63.9 mg g-1 at 30 oC. The kinetic data were best fit with pseudo second-order model. The thermodynamic parameters confirmed a spontaneous endothermic adsorption process. To bring the study to industrial scale, clay granules was made from the natural clay powder and used as fixed bed adsorbent in a column for continuous system. The operational conditions were optimized. Thomas kinetic model was found to fit the experimental kinetic data.
Keywords: Local clay; Adsorption; Nonlinear regression; Fixed bed